(untitled) (Journal of the Society for Musicology in Ireland, 2020)
A review of Kerry Houston, Maria McHale, and Michael Murphy (eds), Irish Musical Studies 12: Documents of Irish Music History in the Long Nineteenth Century (Dublin: Four Courts Press, 2019). ISBN 9781846827242